MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA ANAK USIA 4-5 TAHUN MELALUI MEDIA PUZZLE HURUF DI PAUD (SPS) MIFTAHUSSHIYAN SUKAHAJI CIASEM SUBANG - Siti Nurfaidah; Astuti Darmiyanti; Nur Rochimah (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Early reading skills are basic skills that are important for early childhood as a foundation for language development and readiness to enter the next level of education. However, the reality is that there are still many children aged 4-5 years who have difficulty recognizing letters, distinguishing letter shapes, and stringing letters into simple syllables and words. This research aims to improve the initial reading ability of children aged 4–5 years through the use of letter puzzle media. The research method used is Classroom Action Research (PTK) with the Kemmis and McTaggart models which are carried out in two cycles. The subjects of the study were 10 children of group A at PAUD (SPS) Miftahusshibyan Sukahaji. Data collection techniques include observation, interviews, and documentation. The results of the study show that the use of letter puzzle media can improve children's initial reading skills, both in recognizing letters, distinguishing letters, reading syllables, and reading simple words. Thus, the letter puzzle media is effectively used to improve early reading skills in early childhood. This is evidenced by the data obtained during the pre-action, the percentage reaches %, then increases by % in cycle I to % and increases again by % in cycle II to %. This data shows that puzzle media can improve initial reading ability.